Teknik Permainan Menyusun Kalimat Menggunakan English Card Siswa SMPI Darul Muminin Bekasi - Enny Diah Astuti; Retno Setya Budiasningrum; Jajang Setiawan; Ali Satri Efendi; Rahmi Rosita; Dyan Yuliana (Lembaga Pengembangan Kinerja Dosen, 2024)
English as an international language is an important language to be proficient in since it is used all over the globe. English is not an easy language to learn. Understanding phrases or expressions is very important when speaking English. The foundation for making sentences in English is to first understand words that are often used in everyday life (everyday vocabulary) and being able to effectively construct sentences that can be understood by others is a prerequisite for being able to compose sentences in English. The method used in the implementation of community service at SMPI Darul Muminin Bekasi school is the visual method and English card. The method of forming sentences using English cards emphasizes the ability of students to understand sentences using learnt vocabulary that is used to be assembled in a plot of a story. The application of the game technique method of composing sentences using English cards is considered very effective and fun, it is hoped that one day this method can be used as a model to develop learning activities in the classroom.